Edge influence on understorey plant communities depends on forest management. (5th February 2020) - Govaert, Sanne; Meeussen, Camille; Vanneste, Thomas; Bollmann, Kurt; Brunet, Jörg; Cousins, Sara A. O.; Diekmann, Martin; Graae, Bente J.; Hedwall, Per‐Ola; Heinken, Thilo; Iacopetti, Giovanni; Lenoir, Jonathan; et al.
Abstract: Questions: Does the influence of forest edges on plant species richness and composition depend on forest management? Do forest specialists and generalists show contrasting patterns? Location: Mesic, deciduous forests across Europe. Methods: Vegetation surveys were performed in forests with three management types (unthinned, thinned 5–10 years ago and recently thinned) along a macroclimatic gradient from Italy to Norway. In each of 45 forests, we established five vegetation plots along a south‐facing edge‐to‐interior gradient ( n = 225). Forest specialist, generalist and total species richness, as well as evenness and proportion of specialists, were tested as a function of the management type and distance to the edge while accounting for several environmental variables (e.g. landscape composition and soil characteristics). Magnitude and distance of edge influence were estimated for species richness per management type. Results: Greatest total species richness was found in thinned forests. Edge influence on generalist plant species richness was contingent on the management type, with the smallest decrease in species richness from the edge‐to‐interior in unthinned forests. In addition, generalist richness increased with the proportion of forests in the surrounding landscape and decreased in forests dominated by tree species that cast more shade. Forest specialist species richness, however, was not affected by management type or distance to the edge, and only increased with pH and increasing proportion of forests in the landscape. Conclusions: Forest thinning affects the plant community composition along edge‐to‐interior transects of European forests, with richness of forest specialists and generalists responding differently. Therefore, future studies should take the forest management into account when interpreting edge‐to‐interior because both modify the microclimate, soil processes and deposition of polluting aerosols. This interaction is key to predict the effects of global change on forest plants in landscapes characterized by the mosaic of forest patches and agricultural land that is typical for Europe. Abstract : In Europe, forests are highly fragmented and are often managed. We studied in 9 regions, from Norway to Italy, if edge influence on the understorey depends on forest management. Thinning as forest management did not affect forest specialist species richness negatively in ancient forests, while generalists showed a contrasting pattern.